A technical review of three clinical trials register resources indicates where improvements to the search interfaces are needed. (19th February 2021) - Cooper, Chris; Court, Rachel; Kotas, Eleanor; Schauberger, Ute
Abstract: Clinical trials registers form an important part of the search for studies in systematic reviews of intervention effectiveness but the search interfaces and functionality of registers can be challenging to search systematically and resource intensive to search well. We report a technical review of the search interfaces of three leading trials register resources: ClinicalTrials.gov, the EU Clinical Trials Register and the WHO International Clinical Trials Registers Platform. The technical review used a validated checklist to identify areas where the search interfaces of these trials register resources performed well, where performance was adequate, where performance was poor, and to identify differences between search interfaces. The review found low overall scores for each of the interfaces (ClinicalTrials.gov 55/165, the EU Clinical Trials Register 25/165, the WHO International Clinical Trials Registers Platform 32/165). This finding suggests a need for joined‐up dialogue between the producers of the registers and researchers who search them via these interfaces. We also set out a series of four proposed changes which might improve the search interfaces. Trials registers are an invaluable resource in systematic reviews of intervention effectiveness. With the continued growth in systematic reviews, and initiatives such as 'AllTrials', there is an anticipated need for these resources. We conclude that small changes to the search interfaces, and improved dialogue with providers, might improve the future search functionality of these valuable resources.